Enhanced Axonal Extension of Subcortical Projection Neurons Isolated from Murine Embryonic Cortex using Neuropilin-1 - Sano, Noritaka; Shimogawa, Takafumi; Sakaguchi, Hideya; Ioroi, Yoshihiko; Miyawaki, Yoshifumi; Morizane, Asuka; Miyamoto, Susumu; Takahashi, Jun (Frontiers in Cellular Neuroscience, 2017)
The cerebral cortical tissue of murine embryo and pluripotent stem cell-derived neurons can survive in the brain and extend axons to the spinal cord. For efficient cell integration to the corticospinal tract after transplantation, the induction or selection of cortical motor neurons is important. However, precise information about the appropriate cell population remains unclear. To address this issue, we isolated cells expressing Neuropilin1 (NRP1), a major axon guidance molecule receptor during the early developmental stage, from E14.5 mouse embryonic frontal cortex by fluorescence-activated cell sorting. Aggregates of NRP1+ cells gradually expressed subcortical projection neuron markers, Ctip2 and VGluT1, and axon guidance molecule receptors, Robo1 and Dcc, in vitro, suggesting that they contained early-stage subcortical projection neurons. We transplanted NRP1+ cells into the frontal cortex of P2 neonatal mice. Compared with grafts derived from NRP1− or unsorted cells, those derived from NRP1+ cells extended a larger number of axons to the spinal cord along the corticospinal tract. Our data suggest that sorting NRP1+ cells from the embryonic cerebral cortex enriches subcortical projection neurons to reconstruct the corticospinal tract.